2021
DOI: 10.1128/aem.01676-21
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Metatranscriptomic Characterization of a Microbial Community That Catalyzes Both Energy-Generating and Energy-Storing Electrode Reactions

Abstract: Electroactive bacteria are living catalysts, mediating energy-generating reactions at anodes or energy storage reactions at cathodes via extracellular electron transfer (EET). The Cathode-ANode (CANode) biofilm community was recently shown to facilitate both reactions, however, the identity of the primary constituents and underlying molecular mechanisms remain unknown. Here, we used metagenomics and metatranscriptomics to characterize the CANode biofilm. We show that a previously uncharacterized member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Limited evidence suggests that high frequency does not favor the assembly of electro-methanogenic communities [58, 59]. For example, alternating the polarity every 10 minutes or 2 hours did not lead to the selection of methanogens or Geobacter , and the resulting communities did not produce biogas [60, 61]. It is possible that the alternation frequency should be longer than the doubling time of the populations to be selected so that they have sufficient time to adapt to the electrochemical stimulation [60, 61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited evidence suggests that high frequency does not favor the assembly of electro-methanogenic communities [58, 59]. For example, alternating the polarity every 10 minutes or 2 hours did not lead to the selection of methanogens or Geobacter , and the resulting communities did not produce biogas [60, 61]. It is possible that the alternation frequency should be longer than the doubling time of the populations to be selected so that they have sufficient time to adapt to the electrochemical stimulation [60, 61].…”
Section: Resultsmentioning
confidence: 99%
“…For example, alternating the polarity every 10 minutes or 2 hours did not lead to the selection of methanogens or Geobacter , and the resulting communities did not produce biogas [60, 61]. It is possible that the alternation frequency should be longer than the doubling time of the populations to be selected so that they have sufficient time to adapt to the electrochemical stimulation [60, 61]. Moreover, the alternation frequency can be asymmetric, and a longer cathodic cycle may be more favorable, considering that methanogens typically have a longer doubling time than bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…154 Key enzymes of rTCA and genes for WLP were expressed differently, when reversing the polarity of mixed culture-based bioelectrodes. 155 In a heterogeneous catalyst− microbiome hybrid system, the required genes in both RBO and FAB pathways for MCFA production were identified in metagenomic profiles, whereas only the functional proteins involved in the RBO pathway could be detected by proteomic analysis. 156 In addition, proteomes and metabolomes were used to understand the energy-conservation process for light harvesting and chemical production in CdS-M. thermoacetica hybrid systems (Figure 7f).…”
Section: Characterization Toolsmentioning
confidence: 99%
“…Transcriptional analysis suggested that reductive citric acid cycle (rTCA) and WLP were responsible for CO 2 fixation, regardless of different cathode types . Key enzymes of rTCA and genes for WLP were expressed differently, when reversing the polarity of mixed culture-based bioelectrodes . In a heterogeneous catalyst–microbiome hybrid system, the required genes in both RBO and FAB pathways for MCFA production were identified in metagenomic profiles, whereas only the functional proteins involved in the RBO pathway could be detected by proteomic analysis .…”
Section: Characterization Toolsmentioning
confidence: 99%
“…Some electrochemically active bacteria (EAB) are able to switch between electrogenic and electroautotrophic EET (Ross et al 2011 ; Okamoto et al 2014 ; Yu et al 2015 , 2018 ). This was later further investigated under the term bidirectional EET or canodic (from cathodic + anodic) (Yates et al 2017 ; Mickol et al 2021 ), which implies the ability of EAB to adapt and rapidly transition between electrogenic and -autotrophic EET (Pous et al 2016 ; Yates et al 2017 ; Izadi et al 2021 ; Xie et al 2021 ). This research paved the way for combined bioelectrochemical energy storage (electroautotrophy) and power generation (electrogenesis) in a single device.…”
Section: Introductionmentioning
confidence: 99%